2011
DOI: 10.1002/ijc.25532
|View full text |Cite
|
Sign up to set email alerts
|

Does family history of cancer modify the effects of lifestyle risk factors on esophageal cancer? a population‐based case–control study in China

Abstract: A population-based case-control study on esophageal cancer has been conducted since 2003 in Jiangsu Province, China. The aim of this analysis is to provide further evidence on the relationship between family history of cancer in first-degree relatives (FH-FDRs) and the risk of esophageal cancer, and to explore the joint effects for FH-FDR with major lifestyle risk factors. A total of 1,520 cases and 3,879 controls were recruited. Unconditional logistic regression was applied for evaluating independent associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
5
22
1
Order By: Relevance
“…Family members not only share genetic defects, but also similar environmental factors, such as dietary, smoking, alcohol drinking, and physical habits. Wu et al 24 reported that family history of EsoCa and similar lifestyles act synergistically in a population-based case-control study in China. Up to 3-fold higher risk was observed in individuals with a relative of EsoCa when they have lifestyle risk factors, such as smoking, alcohol, high-sodium diet, consuming very hot foods, and fast-eating speed.…”
Section: 정주원 등 소화기암 가족력이 소화기암 발생에 미치는 위험 평가mentioning
confidence: 99%
See 1 more Smart Citation
“…Family members not only share genetic defects, but also similar environmental factors, such as dietary, smoking, alcohol drinking, and physical habits. Wu et al 24 reported that family history of EsoCa and similar lifestyles act synergistically in a population-based case-control study in China. Up to 3-fold higher risk was observed in individuals with a relative of EsoCa when they have lifestyle risk factors, such as smoking, alcohol, high-sodium diet, consuming very hot foods, and fast-eating speed.…”
Section: 정주원 등 소화기암 가족력이 소화기암 발생에 미치는 위험 평가mentioning
confidence: 99%
“…Up to 3-fold higher risk was observed in individuals with a relative of EsoCa when they have lifestyle risk factors, such as smoking, alcohol, high-sodium diet, consuming very hot foods, and fast-eating speed. 24 Some gene variants associated with CRC development also showed different effects depending on environmental factors, such as intake of vitamin D, calcium, and selenium, as well as smoking habit. 14 These observations in-dicate that a comprehensive lifestyle intervention in these high-risk populations may reduce the incidence of GI cancers.…”
Section: 정주원 등 소화기암 가족력이 소화기암 발생에 미치는 위험 평가mentioning
confidence: 99%
“…In patients, 13.97% subjects were smokers, 29.41% were alcoholic while 11.77% were smokers and alcoholic. Several studies investigating the effects of smoking and alcohol intake on the risk of esophageal cancer have demonstrated that long duration, high consumption and the interaction of these habits may increase the risk of EC (Franceschi et al, 1990;Launoy et al, 1997;Zambon et al, 2000;Castellsague et al, 2004;Lee et al, 2005;Muwonge et al, 2008;Chen et al, 2010;Wu et al, 2011). About 81.62% of patients were from rural background with agriculture as family occupation and 50.74% of them were exposed to pesticides and other agriculture chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…With 386000 annual death, eophageal cancer is the sixth leading cause of cancer death worldwide [12] [13]. The incidence of esophageal cancer is geographically diverse as a large variation could be observed for different parts of the world.…”
Section: Proteomics Of Esophageal Carcinomamentioning
confidence: 99%